2020
DOI: 10.3390/fluids5010018
|View full text |Cite
|
Sign up to set email alerts
|

Volume and Frequency-Independent Spreading of Droplets Driven by Ultrasonic Surface Vibration

Abstract: Many industrial processes depend on the wetting of liquids on various surfaces. Understanding the wetting effects due to ultrasonic vibration could provide a means for changing the behavior of liquids on any surface. In previous studies, low-frequency surface vibrations have been used to alter wetting states of droplets by exciting droplet volume modes. While high-frequency (>20 kHz) surface vibration can also cause droplets to wet or spread on a surface, this effect is relatively uncharacterized. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(59 reference statements)
1
1
0
Order By: Relevance
“…This theory fits very well with the research of Trapuzzano [6] , [20] , who observed that by modifying the vibration amplitude, the contact angle can be modulated.…”
Section: Introductionsupporting
confidence: 90%
“…This theory fits very well with the research of Trapuzzano [6] , [20] , who observed that by modifying the vibration amplitude, the contact angle can be modulated.…”
Section: Introductionsupporting
confidence: 90%
“…It has been studied by many authors, including Lauterborn [13][14][15] and Mason [16], who conclude that the size, number and distribution of bubbles depend mainly on the ultrasonic parameters (amplitude and frequency) and the liquid itself (volume, surface tension, density and viscosity). However, another physical phenomenon has been described by several authors [17][18][19][20]: the contact angle is changed when liquids are exposed to low and high frequency vibration. Manor et al [21] describe a vibration driving force F [N] at megasonic frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Each liquid presents a different atomization threshold [26] that must be adjusted to avoid loss of mass. However, vibration can dramatically increase wettability between solid and liquid phases [27] owing to the vibration-induced force on the surface [28]. This phenomenon helps to form a stable capillary bridge between the vibrating surface and the dirty one.…”
Section: Introductionmentioning
confidence: 99%